Pollen load size, reproductive success and progeny kinship of natural pollinated flowers of the tropical dry forest tree, Pachira quinata (Bombacaceae) - Quesada Avendaño, Mauricio (2001)
Several studies have demonstrated, using controlled pollinations, that the number and identity of pollen grains deposited onto a flower's stigma affect the reproductive success of plants. However, few studies have shown this relationship under conditions of natural pollination. Using the tropical dry forest tree Pachira quinata, we evaluated the relationship between the number of microgametophytes per pistil and the number of sires with respect to the production of fruits and seeds in a natural population of Pachira quinata. Our study demonstrates that fruit and seed production are directly related to the number of microgametophytes per pistil in natural populations of P. quinata. Only 6% of the marked flowers developed into mature fruits and 10% of the marked flowers initiated fruits but later aborted them. A mean of 23 pollen grains were required to produce a seed. Flowers with >400 pollen grains on the stigma always developed into mature fruits, whereas flowers that received <200 grains never matured fruits. Half of the pollen grains transferred to a flower stigma germinated and developed pollen tubes to the base of the style. The number of pollen grains on a stigma explained 34% of the variation in seed number per fruit, and the number of seeds produced per fruit is positively correlated with the size of the seeds. The population of P. quinata studied is predominantly outcrossing, and seeds within fruits are sired by one or a few donors. The total seed crop within trees was sired by three to five donors. Our study examined the implications of the variation in size of microgametophyte loads per pistil with respect to the breeding system and the paternity of progeny under natural conditions. The competitive ability of pollen and pollen tube attrition are important factors regulating fruit production in P. quinata.